Development and validation of a social media and science learning survey. Issue 1 (2nd January 2017) - Moll, Rachel; Nielsen, Wendy
ABSTRACT: The purpose of this study is to describe the development and validation of a survey that examines science students' social media learning behaviours. Inherent in critiques regarding 'digital natives' is a need to better understand what the current generation of learners actually do in their social media practices for learning . The survey can help us understand how students actually use social media for learning science. Survey development followed an inductive approach [Brinkman, 2013. Qualitative interviewing . Oxford ebook; Mansourian, 2006. Adoption of grounded theory in LIS research. New Library World, 107(9/10), 386–402; Strauss & Corbin, 1998. Basics of qualitative research: Grounded theory procedures and technique (2nd ed.). Newbury Park, CA: Sage], where survey design was informed by results of focus groups with secondary and post-secondary physics students and the survey was iteratively revised after two cycles of administration and validation interviews. The final version of the Social Media and Science Learning Survey can be used by educators and researchers to understand how social media tools can be leveraged in order to allow learning to emerge and to use this knowledge to frame recommendations and methods for integrating these tools into classroom-based environments.